HEMODYNAMIC STABILITY OF HYPERTENSION PATIENT: TRIPLE THERAPY OPPORTUNITIES - N. G. Poteshkina; N. S. Krylova; А. М. Svanadze; А. А. Troshina (Российский кардиологический журнал)
The article is focused on the review of recent epidemiological and clinical data on the prevalence of systemic hypertension and its influence on the outcomes of cardiovascular diseases. An efficacy is argued, as the adherence for and safety of antihypertension therapy by combinational drug “single-pill” Triplixam® (“Les Laboratoires Servier”, France), containing perindopril/indapamide/amlodipine. The usage of the medication is grounded, aiming against target organ damage and development of cardiovascular outcomes.